PENGARUH RENTABILITAS DAN LEVERAGE PADA KEPUTUSAN SAHAM BONUS DAN IMPLIKASINYA PADA NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Yang Mengeluarkan Saham Bonus di Bursa Efek Indonesia) - Larasdiputra, Gde Deny; Yadnyana, I Ketut; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study was to find out what can influence the occurrence of the bonus shares with a view of the variable rentability and leverage of the company. This study will also reveal the market's reaction as a result of the announcement of bonus shares. The data used are secondary data from the financial statements and annual reports of companies listed on the Indonesia Stock Exchange in 2000-2014. Selection of the sample with purposive sampling method and acquired 36 companies with a number of observations over 14 years. Data analysis technique used is path analysis. These results indicate that, if high corporate rentability, the company tends to pay dividends and vice versa. Bonus issue itself was published at a time when companies do not have the capability sufficient cash to pay dividends, and the company will choose a stock option bonus as a successor or the company entered into a plan of dividend reinvestment plans (DRP) which allows investors to reinvest the dividends they have received returned to the company as additional capital for the company and instead investors receive bonus shares of the company. The results of this study also indicate that the market reacted positively to the announcement of bonus share.
Keywords: Keywords: Rentability, Leverage, Bonus Share, Company Value